Transsynaptic N-Cadherin Adhesion Complexes Control Presynaptic Vesicle and Bulk Endocytosis at Physiological Temperature - Dagar, Sushma; Teng, Zenghui; Gottmann, Kurt (Frontiers in Cellular Neuroscience, 2021)
At mammalian glutamatergic synapses, most basic elements of synaptic transmission have been shown to be modulated by specific transsynaptic adhesion complexes. However, although crucial for synapse homeostasis, a physiological regulation of synaptic vesicle endocytosis by adhesion molecules has not been firmly established. The homophilic adhesion protein N-cadherin is localized at the peri-active zone, where the highly temperature dependent endocytosis of vesicles occurs. Here, we demonstrate an important modulatory role of N-cadherin in endocytosis at near physiological temperature by synaptophysin-pHluorin imaging. Different modes of endocytosis including bulk endocytosis were dependent on N-cadherin expression and function. N-cadherin modulation was mediated by actin filaments, because actin polymerization rescued the knockout induced endocytosis defect. Using super-resolution imaging, we found a strong recruitment of N-cadherin to glutamatergic synapses upon massive vesicle release, which might in turn enhance vesicle endocytosis. This provides a novel, adhesion protein mediated mechanism for efficient coupling of exo- and endocytosis.